An Empirical Modelling of New Zealand Hospitality and Tourism Stock Returns. (26th February 2013) - Lim, Christine; Chan, Felix
Abstract : This paper examines the factor risk premiums of stock returns for the hospitality and tourism companies in New Zealand. The Arbitrage Pricing Theory (APT) approach is used to investigate the expected return for stock portfolio with respect to market, macro (i.e., money supply and discount rate), and tourism factor sensitivities. Monthly stock prices, market index, tourism, and macroeconomic data are used in the study. The results indicate that the risk premiums for international tourism demand and term premium (proxy for discount rate) are positively significant at the 5% level. A one unit increase in tourist arrival sensitivity would result in expected return increase of 10 to 17 percentage point. Similarly, a one unit increase in term premium can increase hospitality-tourism expected returns by 0.2 percentage point. However, the findings for the money supply factor are not significant. As the study shows that investors face high positive tourism demand risk, it is imperative for firms and policymakers in New Zealand to promote inbound tourism through effective marketing and management. This in turn can provide high expected returns and create shareholder value for investors.